(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Translocal livelihoods and circular migration characterise the interdependence of rural and urban areas in southern Africa. This study analyses demographic, socio-economic and environmental dimensions of translocal dynamics at the household level in rural north-central Namibia from 1943 to 2012. Special emphasis is placed on the impact of internal migration on the age and sex structure of rural and urban communities, an aspect which has been largely neglected in research to date. Our analysis of the population data shows that the most visible indication of translocality is the distorted age structure of the resident population. Able-bodied persons, particularly males, were virtually absent in many of the homesteads. The empirical evidence from north-central Namibia shows that circular migration has become an essential part of the adaptation strategy of rural households in a changing socio-economic environment. In this context, the improvement of women’s land rights indicates change towards a more gender-equal society.